2020
DOI: 10.3390/coatings10050437
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Deflection Prediction of Piezo-Composite Unimorph Actuator Using Material Orthotropy and Nonlinearity of Piezoelectric Material Layer

Abstract: Layered piezo-composite unimorph actuators have been studied by many research teams to provide active vibration control of thin-walled aerospace structures, control the shapes of aircraft wing airfoils, and control the fins of small missiles, because they require less space and provide better frequency responses than conventional electro-magnetic motor actuator systems. However, due to the limited actuation strains of conventional piezo-composite unimorph actuators with poly-crystalline piezoelectric ceramic l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Curved piezoelectric structures exhibit differences in strain mode, charge distribution and material requirements compared to other piezoelectric structures. Lee et al [17] found that the lightweight piezocomposite unimorph actuator (LIPCA-S2) with a cantilever length of 65 mm achieves a maximum tip displacement of 15.2 mm, with an average inverse piezoelectric constant of 1100 pm/V. Given its lightweight and small size, LIPCA-S2 could be used in aerodynamic-related fields such as spacecraft wing section control and small missile guidance.…”
Section: Curved Surface and Porous Structurementioning
confidence: 99%
“…Curved piezoelectric structures exhibit differences in strain mode, charge distribution and material requirements compared to other piezoelectric structures. Lee et al [17] found that the lightweight piezocomposite unimorph actuator (LIPCA-S2) with a cantilever length of 65 mm achieves a maximum tip displacement of 15.2 mm, with an average inverse piezoelectric constant of 1100 pm/V. Given its lightweight and small size, LIPCA-S2 could be used in aerodynamic-related fields such as spacecraft wing section control and small missile guidance.…”
Section: Curved Surface and Porous Structurementioning
confidence: 99%
“…Dielectric materials with pronounced piezo effect are used in the fabrication of actuators [1], energy harvesting systems, crystal oscillators, surface acoustic wave filters, sensors, and MEMS [2]. The piezo effect is observed for the first time in Rochelle salt [3].…”
Section: Introductionmentioning
confidence: 99%